PENGARUH STRATEGI PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DAN GAYA BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA - Berkat Johannes Pakpahan (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
This research was aimed to find out : (1) the difference of achievement inindonesian language between Problem Based Learning instructional strategy andexpository instructional strategy, (2) the difference of achievement in Indonesianlanguage between student’s who had visual learning style and auditorial learningstyle, (3) interaction between instructional strategy and the learning style on thestudents’ achievement in Indonesian language.The population of this research was all of class VIII of students SMPParulian 2 Medan, which had 120 students, that consist of three classes. The samplewas taken by using cluster random sampling method. The total sample of theresearch for instructional strategy which 40 students’ taught by Problem BasedLearning instructional strategy and 40 students’ done by learning of expositoryinstructional strategy. Instrument scale for Indonesian language achievement thatused to measure the achievement of Indonesian’s language had coefficient 0,82. Theresearch method used quasi experiment with factorial design 2x2. Technique ofanalyzing data used two ways ANAVA at significant α = 0,05.The finding of the research showed that : (1) the students’ achievement inIndonesian language that taught by Problem Based Learning instructional strategy( X = 83,45), is higher than the students’ achievement that taught by expositoryinstructional strategy ( X = 64,2), dengan hitung F = 36,26 > tabel F = 3,97 , (2) thestudents’ achievement in Indonesian language with visual learning style ( X = 76,86)is higher than auditorial learning style ( X = 70,03), with ratio F = 64,80 > table F =3,97, (3) be found interaction between instructional strategy and the learning styleon the students’ achievement in Indonesian language, with ratio F = 15,13 > table F =3,97. The multiple comparation by Scheffe test also showed significant difference ofachievement in Indonesian language between Problem Based Learning instructionalstrategy and expository instructional strategy, similar with achievement inIndonesian language between visual learning style and auditorial learning style.